“Sheikh Abdurrauf Kang Abangsa Syekh Hamzah Fansuri”: Examining the Relationship Between Two - Ramli, Ramli (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
The phrase